A review of the use and potential of the GATE Monte Carlo simulation code for radiation therapy and dosimetry applications. Issue 6 (12th May 2014) - Sarrut, David; Bardiès, Manuel; Boussion, Nicolas; Freud, Nicolas; Jan, Sébastien; Létang, Jean‐Michel; Loudos, George; Maigne, Lydia; Marcatili, Sara; Mauxion, Thibault; Papadimitroulas, Panagiotis; Perrot, Yann; et al.
Abstract : In this paper, the authors' review the applicability of the open‐source GATE Monte Carlo simulation platform based on the GEANT4 toolkit for radiation therapy and dosimetry applications. The many applications of GATE for state‐of‐the‐art radiotherapy simulations are described including external beam radiotherapy, brachytherapy, intraoperative radiotherapy, hadrontherapy, molecular radiotherapy, and in vivo dose monitoring. Investigations that have been performed using GEANT4 only are also mentioned to illustrate the potential of GATE. The very practical feature of GATE making it easy to model both a treatment and an imaging acquisition within the same frameworkis emphasized. The computational times associated with several applications are provided to illustrate the practical feasibility of the simulations using current computing facilities.